SERVICE QUALITY, CUSTOMER SERVICE QUALITY, CUSTOMER SATISFACTION, DAN CORPORATE IMAGE TERHADAP CUSTOMER LOYALTY PADA KLINIK KECANTIKAN DI JAKARTA - MEGI TAMIA; WIBISONO SOEDIONO (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2019)
The purpose of this research to aware of the influence of service quality, customer satisfaction, and corporate image, toward customer loyalty on klinik kecantikan erha skin care at Jakarta. This study using regression analysis to analyse data. The research has 100 sample on klinik kecantikan erha skin care. Research used purposive sampling method to determine this study. This study found that service quality, customer satisfaction and corporate image good effect on customer loyalty on klinik kecantikan erha skin care in Jakarta.